Sharing a voice: early-career scholars and the arctic - Kyriakou, Aristea; Loovers, Jan Peter Laurens; Moir, Annette; Peers, Eleanor; Ruiter, Keith (University of Aberdeen Press, 2018)
At the University of the Arctic Rectors’ Forum, held on 23rd of August 2017 at the University of Aberdeen, Early-Career Scholars collaboratively developed a proposal on the Forum theme of The Inhabited Arctic: Lands, Peoples and Scholarship in the Circumpolar North. This interdisciplinary group focused on developing opportunities in circumpolar scholarship, tackling the pressing challenges of geopolitical circumstances, scarce research funding and shifting national agendas. The following feature embodies a shared voice focussed on promoting capacity building in the UArctic and enhancing accessibility of teaching and research in the North. The wider recognition of this shared voice is vital for sustainability.